A study of bank efficiency taking into account risk-preferences - Mester, Loretta J. (Journal of Banking & Finance, 1996)
I use the stochastic cost frontier approach to investigate efficiency of banks operating in the Third Federal Reserve District, accounting for the quality and riskiness of bank output. In addition to the mean and mode of the conditional distribution of the one-sided error term, I calculate confidence intervals for the inefficiency measures based on the conditional distribution. The results indicate that Third District banks are operating at cost-efficient output levels and product mixes, but are not efficiently using their inputs. The second part of the article relates the inefficiency measures to several correlates.